Guidance on prevention of unintended and accidental radiation exposures in nuclear medicine. (4th June 2019) - Martin, C J; Marengo, M; Vassileva, J; Giammarile, F; Poli, G L; Marks, P
Abstract: Nuclear medicine (NM) procedures for diagnosis and treatment of disease are performed routinely in hospitals throughout the world. These involve preparation and administration to patients of pharmaceuticals labelled with radioactive material. The International Atomic Energy Agency (IAEA) and the World Health Organisation highlighted the need for improvement in prevention of medical radiation incidents and accidents in the Bonn Call-for-Action in 2012. An IAEA Technical Meeting was held on prevention of unintended exposures and accidents in NM in 2018 to address the issue. Exposures can take place at any time when radioactive material is being produced and used, and the risk continues after procedures have been completed. Thus there is potential for staff or members of the general public to be exposed, as well as patients. This paper sets out guidelines for incident prevention based on presentations and discussions at the meeting, and review of reports from the literature. It deals with potential incidents in in-house radionuclide production, radiopharmaceutical preparation, administration to patients, and following a procedure, as well as aspects in management of radioactive materials. Special attention has been paid to therapeutic procedures, as these have the potential to cause more harm to patients from erroneous administrations, including tissue reactions from extravasation of radiopharmaceutical, and could lead to significant contamination events. Administration of NM therapy is generally contraindicated in pregnancy. Identification of any patient who may be pregnant is crucial and it might be necessary to verify this with a pregnancy test for patients within the age band considered to be fertile. Inclusion of NM therapy incidents in the IAEA automated reporting system SAFRON is recommended. In summary, the paper aims to highlight errors that could occur during different phases of NM procedures in order to aid prevention of incidents. The value of periodic audit in evaluating systems in place on a regular basis is emphasised. Approaches to incident investigation and follow-up are described, and the need to ensure corrective action is taken to address any deficiencies stressed.